Astroglial CB1 Cannabinoid Receptors Mediate CP 55,940-Induced Conditioned Place Aversion Through Cyclooxygenase-2 Signaling in Mice - Cong, Jin; Lu, Kangrong; Zou, Wenjie; Li, Ziming; Guo, Zhipeng; Tong, Xiangzhen; Zheng, Jiawei; Zhu, Jianping; Li, Shuji; Zhang, Wangming; Guo, Yanwu; Gao, Tian-Ming; et al. (Frontiers in Cellular Neuroscience, 2021)
Cannabinoids, including phytocannabinoids, synthetic cannabinoids and endogenous cannabinoids, can be neuroprotective, rewarding or aversive. The aversive effects of cannabinoids may hinder their medical and recreational applications. It is unknown which type of cannabinoid (CB) receptors mediates the direct aversive effects of synthetic cannabinoid CP 55,940 which is an analog of Δ9-THC (Δ9-tetrahydrocannabinol), the major psychoactive component of marijuana. In this study, we address this question by taking advantage of systematic type 1 CB receptor (CB1R) knockout mice and conditional reinstatement of this receptor only in astrocytes. We show that CP 55,940 at a concentration of 1 mg/kg induces conditioned place aversion (CPA) and the CPA effect of CP 55,940 is mediated by astroglial CB1Rs. Inhibiting cyclooxygenase-2 (COX-2) eliminates CP 55,940-induced CPA in mice that only express CB1Rs in astrocytes. These findings conclude that CPA effect of CP 55,940 is mediated by astroglial CB1 cannabinoid receptors through COX-2 signaling, suggesting that selective COX-2 inhibition or precise isolation of astroglial CB1Rs activity may be the strategy for treating aversive response of medical and recreational administrations of marijuana.